ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN - Pradipta, Dedik Norman; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out empirical evidences about some factors which influence the timeliness offinancial report of manufacturing company which is listed in Indonesia Stock Exchange. Factors which beingtested in this research is firm size, profitability, debt to equity ratio, auditor quality, and audit opinion. Thesamples of this research are 207 manufacturing companies which are listed in Indonesia Stock Exchange in2012-2014 periods and these manufacturing companies have been taken by using purposive sampling method.These factors then are tested by using logistic regressions and its significance level is 5 percent.The result of thisresearch has identified that firm size, profitability, debt to equity ratio and auditor quality has significantinfluence to the timeliness of financial reporting, meanwhile audit opinion does not have any influence to thetimeliness of financial statement of manufacturing companies which are listed in Indonesia Stock Exchange.This is due to the audit opinion on the financial statements drawn up does not affect the management to delivera robust set of reports right or not timeliness.Keywords: timeliness, firm size, financial ratio, auditor quality, audit opinion.